Anodal tDCS Over the Left Frontal Eye Field Improves Sustained Visual Search Performance. (April 2022) - Gan, Tian; Huang, Yanyan; Hao, Xin; Hu, Lina; Zheng, Yan; Yang, Zhen
Monotonous and repetitive tasks cause vigilance, or sustained attention decrement, which possibly leads to irreparable accident consequences in the aerospace and nuclear industry. Buffering the decrement of vigilance in visual search tasks is essential for cognitive enhancement and ergonomic research. This study aimed to evaluate the efficacy of anodal transcranial direct current stimulation (tDCS) applied to the left frontal eye field (FEF) to improve the performance of the sustained visual search. Twenty-seven healthy participants received anodal and sham tDCS of 2 mA for 28.8 min and completed a visual search task lasting for approximately 40 min without any break. For the online effect, results showed that the d′ hit rate and accuracy under anodal tDCS were significantly higher than those under sham conditions during 0–19.2 min time intervals. For the after-effect, compared with sham, anodal tDCS caused significantly higher d′ in the 10 min after completing the tDCS. Our findings suggest that anodal tDCS over the left FEF could effectively mitigate the decline of visual vigilance performance by buffering cognitive resource depletion.